A Low‐Temperature Sodium‐Ion Full Battery: Superb Kinetics and Cycling Stability. (18th December 2020) - Rui, Xianhong; Zhang, Xianghua; Xu, Shitan; Tan, Huiteng; Jiang, Yu; Gan, Li Yong; Feng, Yuezhan; Li, Cheng Chao; Yu, Yan
Abstract: The increasingly stringent requirement in large‐scale energy storage necessitates the development of high‐performance sodium‐ion batteries (SIBs) that can operate under low‐temperature (LT) environment. Although SIBs can achieve good cycling stability and rate performance at room temperature, the sluggish electrochemical reaction kinetics at low temperature remains a great challenge for SIBs. Here, a superior LT SIB composed of 3D porous Na3 V2 (PO4 )3 /C (NVP/C‐F) and NaTi2 (PO4 )3 /C foams (NTP/C‐F) is developed. First‐principles calculations reveal that the intrinsic Na + diffusivity in NASICON‐type NVP and NTP is extremely high (maximum 3.84 × 10 −5 for NVP and 2.94 × 10 −9 cm 2 s −1 for NTP) at –20 °C. In addition, the designed 3D interconnected porous foam structures demonstrate excellent electrolyte absorption ability and Na + transport performance at low temperature. As a result, under −20 °C, the NVP/CF and NTP/CF electrodes (half‐cell configuration) can attain reversible capacities close to their theoretical values, and are able to be charged and discharged rapidly (20 C) for 1000 cycles. Based on these features, the designed NTP/CF||NVP/CF full cell also displays superb LT kinetics and cycling stability, making a great stride forward in the development of LT SIBs. Abstract : A high‐performance low‐temperature sodium ion full battery composed of 3D porous Na3 V2 (PO4 )3 /C and NaTi2 (PO4 )3 /C foams is developed. Owing to the fast Na + diffusivity of these two NASICON‐type electrodes and excellent electrolyte absorption ability of the foam structure, this full battery demonstrates superb kinetics and cycling stability (e.g., 20 C over 1000 cycles) at −20 °C.